Revision of the Neotropical subfamily Eurychoromyiinae (Diptera: Lauxaniidae) - Gaimari, Stephen D.; Silva, Vera C. [UNESP] (Magnolia Press, 2010)
The status of the enigmatic family Eurychoromyiidae is revised to a subfamily of Lauxaniidae, and the entire subfamily is revised with a key to genera and species, and maps for all species. Previously monotypic with only the species Eurychoromyia mallea Hendel, one closely related genus, Tauridion Papp & Silva, is moved into this subfamily, and five new genera are described: Choryeuromyia, Euryhendelimyia, Eurystratiomyia, Physegeniopsis, and Roryeuchomyia. Besides the type species for Eurychoromyia and Tauridion, all species herein are new, including Choryeuromyia xenisma (type species of genus), Euryhendelimyia schlingeri (type species of genus), Eurystratiomyia epacrovitta, Eurystratiomyia erwini (type species of genus), Physegeniopsis albeto, Physegeniopsis ankhoidea (type species of genus), Physegeniopsis hadrocara, and Roryeuchomyia tigrina (type species of genus). Eggs are described for Tauridion shewelli and Physegeniopsis albeto.
Keywords: Diptera; Lauxaniidae; Eurychoromyiidae; Choryeuromyia; Eurychoromyia; Euryhendelimyia; Eurystratiomyia; Physegeniopsis; Roryeuchomyia; Tauridion; Neotropical